Evidence from cyclostomes for complex regionalization of the ancestral vertebrate brain. - Sugahara, Fumiaki; Pascual-Anaya, Juan; Oisi, Yasuhiro; Kuraku, Shigehiro; Aota, Shin-ichi; Adachi, Noritaka; Takagi, Wataru; Hirai, Tamami; Murakami, Yasunori; Kuratani, Shigeru (Nature Research, 2016)
The vertebrate brain is highly complex, but its evolutionary origin remains elusive. Because of the absence of certain developmental domains generally marked by the expression of regulatory genes, the embryonic brain of the lamprey, a jawless vertebrate, had been regarded as representing a less complex, ancestral state of the vertebrate brain. Specifically, the absence of a Hedgehog- and Nkx2.1-positive domain in the lamprey subpallium was thought to be similar to mouse mutants in which the suppression of Nkx2-1 leads to a loss of the medial ganglionic eminence. Here we show that the brain of the inshore hagfish (Eptatretus burgeri), another cyclostome group, develops domains equivalent to the medial ganglionic eminence and rhombic lip, resembling the gnathostome brain. Moreover, further investigation of lamprey larvae revealed that these domains are also present, ruling out the possibility of convergent evolution between hagfish and gnathostomes. Thus, brain regionalization as seen in crown gnathostomes is not an evolutionary innovation of this group, but dates back to the latest vertebrate ancestor before the divergence of cyclostomes and gnathostomes more than 500 million years ago.
https://v2.sherpa.ac.uk/id/publication/4008
Keywords: Cerebro - Evolución; Lampreas; Evolución del Cerebro; Mixino; Lampreas; Vertebrados